2017
DOI: 10.1016/j.apsoil.2017.09.027
|View full text |Cite
|
Sign up to set email alerts
|

The ‘terril’ effect: Coal mine spoil tips select for collembolan functional traits in post-mining landscapes of northern France

Abstract: We sampled collembolan communities in 11 coal mine spoil tips (locally called 'terrils') from the North of France, and their surroundings, in various stages of vegetation development (bare soil, herb, shrub and tree vegetation). We wondered whether species, functional trait (Community Weighted Mean trait or CWM) composition and trait diversity (Rao's quadratic entropy) responded to the particular environment of coal mine spoil tips (here called 'terril' effect) and to successional effects and which of these th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 104 publications
(139 reference statements)
5
13
0
Order By: Relevance
“…Collembola and macrofauna communities can be both affected by surrounding environment and vegetation in derelict soils (Cortet et al, 2013;Baranova et al, 2014;Vanhee et al, 2017). Although no geostatistical analyses were performed in the present study, some hypotheses might be suggested on species traits selection.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Collembola and macrofauna communities can be both affected by surrounding environment and vegetation in derelict soils (Cortet et al, 2013;Baranova et al, 2014;Vanhee et al, 2017). Although no geostatistical analyses were performed in the present study, some hypotheses might be suggested on species traits selection.…”
Section: Discussionmentioning
confidence: 75%
“…Firstly, the OM content was associated with the presence of Collembola Lepidocyrtus lanuginosus and Isotomiella minor, found at high densities in soils with high OM contents (Santorufo et al, 2014) and in coal mine spoil tip soils (Vanhee et al, 2017). These species are considered as forest-inhabiting species (Heiniger et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For soil restoration, the objective is to maintain the functional ecology, providing essential functions and ecosystem services. In light of this, the functional diversity approach must be promoted 9 , with an interest on functional traits rather than species 10 . However, for soil biodiversity conservation, environmental actions should promote the importance of local, natural heritage and hence should consider the site effect on species composition.…”
Section: Introductionmentioning
confidence: 99%
“…The active motility of collembolan species is highly variable, depending on whether animals are adapted to subterranean or aerial life and whether they possess organs making them able to walk or jump (Vanhee et al 2017). By active movement they are able to select habitats within a circle of up to 200m, above which dispersal limitation is commonly observed at community level (Ponge and Salmon 2013).…”
Section: Why and How To Move?mentioning
confidence: 99%